FOSTERING STUDENTS’ PRONUNCIATION BY USING WHISPERING TONGUE TWISTER - Asriani; Maming, Khadijah; Sianna; Sahabuddin, Ilham (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study was designed based on the results of observations of the pronunciation skills of eighth grade students at SMPN 1 Parepare, South Sulawesi. Many average students' pronunciation skills are categorized as low, making it difficult to speak English. The researcherss provide solutions by teaching pronunciation using the whispering tongue twister method to students with the concept of playing while learning. Therefore, the purpose of this study is to find out whether the use of the whispering Tongue Twister method can help students' pronunciation. The researcherss used the pre-experimental method with a group pretest and post-test design. The population of this study included all VIII grade students at SMPN 1 Parepare, with a sample size of 32 students in class VIII.4 as the experimental class. The sample selection used the purposive sampling technique and data collection using pretest and post-tests with the text read. The treatment was done in four meetings with two aspects of assessment, namely accuracy and fluency. In analyzing the data, researcherss used SPSS 29. The results of the data analysis show an improvement in student pronunciation. This is evidenced by the average score on the initial test of students, which is 33.84 and the average score on the final test of students, which is 45.84. After analyzing the data, the result of the probability is 0.001 and the significance value is 0.05. This indicates that H0 was rejected and H1 was rejected. It can be concluded that the use of the Whispering Tongue Twister method can foster students' pronunciation at SMPN 1 Parepare in the 2023/2024 school year.